3D printing of continuous fiber reinforced composites: A review of the processing, pre- and post-processing effects on mechanical properties. (26th April 2022) - Safari, Faraz; Kami, Abdolvahed; Abedini, Vahid
The main objective of this study is to review existing research on the application of fused deposition modeling (FDM) for 3D printing of continuous fiber reinforced composites (CFRCs). An overview of additive manufacturing technology production techniques is provided first, followed by a look into FDM technology. The articles on CFRC printing were then summarized. The type of reinforcing material and matrix utilized, the studied parameters, the mechanical tests, and their results, are all listed. Various pre-processing, processing, and post-processing conditions, as well as their impact on CFRC mechanical properties, were also discussed. Finally, several study gaps were identified and suggestions for further research were presented. Graphical Abstract